Brief communication: Effect of size biases in the coefficient of variation on assessing intraspecific variability in the prosimian skeleton. Issue 1 (30th July 2013) - Fulwood, Ethan L.; Kramer, Andrew
ABSTRACT This study examines the effect of a measurement size bias in coefficients of variation on the evaluation of intraspecific skeletal variability in a sample of eight prosimian species (Eulemur fulvus, Hapalemur griseus, Lemur catta, Varecia variegata, Galago senegalensis, Otolemur crassicaudatus, Nycticebus coucang, and Tarsius syrichta). Measurements with smaller means were expected to have higher coefficients of variation (CVs) due to the impact of instrumental precision on the ability to assess variability. This was evaluated by testing for a negative correlation between CVs and means in the total sample, within each species, and within each measurement, and by testing for the leveraging impact of small measurements on the significance of comparisons of variability between regions of the prosimian skeleton. Three comparisons were made: cranial versus postcranial variability, epiphysis versus diaphysis variability, and forelimb versus hindlimb variability. CVs were significantly negatively correlated with means within the total sample (r2= 0.208, P < 0.0001) and within each species. CVs and means were significantly correlated within only three of the measurements, which may reflect the relatively low body size range of the species studied. As predicted by the higher variability of smaller measurements, removing the smallest measurements from comparisons of variable classes containing measurements of different mean magnitudes pushed the comparisons below significance. These results indicate caution should be exercised when using CVs to assess variability across sets of measurements with different means. Am J Phys Anthropol 152:151–155, 2013. © 2013 Wiley Periodicals, Inc.